Contrasting performance between physically active and sedentary older people playing exergames. Issue 5 (February 2019) - Zangirolami-Raimundo, Juliana; Raimundo, Rodrigo Daminello; da Silva, Talita Dias; de Andrade, Paulo Evaristo; Benetti, Fernanda Antico; da Silva Paiva, Laércio; do Valle, Joseane Elza Tonussi Mendes Rossette; de Abreu, Luiz Carlos
Abstract : Abstract: The increase in life expectancy associated with the increase in chronological age and less active people helps in the appearance of chronic and degenerative diseases. The encouragement of physical exercises contributes to older people abandoning sedentarism and preventing such diseases. Exergame is a promising alternative, for making exercise a pleasurable activity. In this study, we compared the performance of physically active older people with sedentary older people in exergames. Participants were 83 older adults over 65 years of age, of both sexes, divided into 2 physically active older people (AG) and sedentary older people (CG) groups. The participants performed a task through an exergame called "MoviLetrando" that uses the score, number of hits, number of omissions, and an average time of hits as an evaluation. A characterization questionnaire was applied, with information about sex, age, marital status, economic class, self-rated health, time of use of electronic games, a questionnaire on the practice of physical activity, and the Brunel Mood Scale. There was a higher exergame score in AG than in CG ( P = .003), in the number of correct answers ( P = .012). The number of omissions was lower in AG than in CG ( P = .023). The mean time of correct answers was lower in AG than in CG ( P = .013). The regression analysis revealed a significant finding F (3, 82) = 11.06, P < .001 and showed a prediction ability of 26.9% ( r 2 = .269). Three variables remained significantly associated with the score: physical activity was marginally significant (β = .19, P = .06), age (β = −.403, P < .001), depression (β = −.212, P = .028). Physically active older people perform better when compared with the sedentary older people. Age, depression, and physical activity influence the performance in exergame.